Demonstration of the role of cell wall homeostasis in Staphylococcus aureus growth and the action of bactericidal antibiotics - Salamaga, Bartłomiej; Kong, Lingyuan; Pasquina-Lemonche, Laia; Lafage, Lucia; von Und Zur Muhlen, Milena; Gibson, Josie F; Grybchuk, Danyil; Tooke, Amy K; Panchal, Viralkumar; Culp, Elizabeth J; Tatham, Elizabeth; O'Kane, Mary E; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Bacterial cell wall peptidoglycan is essential, maintaining both cellular integrity and morphology, in the face of internal turgor pressure. Peptidoglycan synthesis is important, as it is targeted by cell wall antibiotics, including methicillin and vancomycin. Here, we have used the major human pathogen Staphylococcus aureus to elucidate both the cell wall dynamic processes essential for growth (life) and the bactericidal effects of cell wall antibiotics (death) based on the principle of coordinated peptidoglycan synthesis and hydrolysis. The death of S. aureus due to depletion of the essential, two-component and positive regulatory system for peptidoglycan hydrolase activity (WalKR) is prevented by addition of otherwise bactericidal cell wall antibiotics, resulting in stasis. In contrast, cell wall antibiotics kill via the activity of peptidoglycan hydrolases in the absence of concomitant synthesis. Both methicillin and vancomycin treatment lead to the appearance of perforating holes throughout the cell wall due to peptidoglycan hydrolases. Methicillin alone also results in plasmolysis and misshapen septa with the involvement of the major peptidoglycan hydrolase Atl, a process that is inhibited by vancomycin. The bactericidal effect of vancomycin involves the peptidoglycan hydrolase SagB. In the presence of cell wall antibiotics, the inhibition of peptidoglycan hydrolase activity using the inhibitor complestatin results in reduced killing, while, conversely, the deregulation of hydrolase activity via loss of wall teichoic acids increases the death rate. For S. aureus, the independent regulation of cell wall synthesis and hydrolysis can lead to cell growth, death, or stasis, with implications for the development of new control regimes for this important pathogen.
Keywords: homeostáza; stafylokokové infekce; kyseliny teichoové; Peptidoglycan; Bacterial Proteins; Staphylococcus aureus; peptidoglycan; antibakteriální látky; Homeostasis; Vancomycin; antibiotics; Anti-Infective Agents; N-Acetylmuramoyl-L-alanine Amidase; N-acetylmuramoyl-L-alaninamidasa; Teichoic Acids; cell wall; buněčná stěna; Cell Wall; Anti-Bacterial Agents; Methicillin; peptidoglykan; bakteriální proteiny; Staphylococcal Infections; vankomycin; vancomycin; methicillin; antiinfekční látky; methicilin